Creating Urban and Building Space for Agricultural Space Towards Sustainable Jakarta - Prawata, Albertus (Bina Nusantara University, 2013)
Agricultural sector will be one of the many sectors affected by the rapid growing population in the cities. The agricultural crisis would lead to more dependence on imports for food. Another problem caused by the rapid growing population is the relocation of agriculture industries to the countryside. This will result inhigher price for food, air pollution, and traffic jam. Indoor controlled environment agriculture is one of the strategies that can help the city, so it can produce its own food and create sustainable lifestyle. This paper focuses on how to create Jakarta, one of the big cities in South East Asia, into a city based on agricultural system that can ensure food safety and make a sustainable urban lifestyle without damaging the environment. Also, it discusses the possibilities of converting the urban or building space into agricultural space, which can support the food production for the people of Jakarta.